2017
DOI: 10.1373/clinchem.2017.278267
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Total Protein Reference Intervals Derived from 20 Years of Patient Data

Abstract: The age dependence of CSF-TP supports that age-partitioned reference intervals will be more accurate than a single cutoff, particularly in patients with advancing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 11 publications
10
69
0
Order By: Relevance
“…While more than 85% of laboratories worldwide consider 0.45 g/L to be the upper CSF reference limit, lower or higher reference limits are occasionally utilized [33]. Several studies have shown that the widely used cutoff of 0.45 g/L is erroneously low [34,35]. Implementation of CSF values of 0.50 g/L for patients aged B 50 years and 0.60 g/L for those aged [ 50 years have been proposed as a better standard CSF reference value [36].…”
Section: Laboratory Pitfallsmentioning
confidence: 99%
“…While more than 85% of laboratories worldwide consider 0.45 g/L to be the upper CSF reference limit, lower or higher reference limits are occasionally utilized [33]. Several studies have shown that the widely used cutoff of 0.45 g/L is erroneously low [34,35]. Implementation of CSF values of 0.50 g/L for patients aged B 50 years and 0.60 g/L for those aged [ 50 years have been proposed as a better standard CSF reference value [36].…”
Section: Laboratory Pitfallsmentioning
confidence: 99%
“…There is now ample evidence indicating that the URL for CSF‐TP should be partitioned by age and that the widely used 45 mg/dl upper limit is erroneously low . The adoption of 45 mg/dl as the URL was based on the publication in 1938 of a study that sampled a reference population of younger patients.…”
mentioning
confidence: 99%
“…There is now ample evidence indicating that the URL for CSF-TP should be partitioned by age and that the widely used 45 mg/dl upper limit is erroneously low. 9,11 The adoption of 45 mg/dl as the URL was based on the publication in 1938 12 of a study that sampled a reference population of younger patients. Moreover, recent laboratory studies and a systematic review of the literature support implementation of CSF URL values of 50 mg/dl for patients aged ≤50 years and 60 mg/dl for those aged >50 years.…”
mentioning
confidence: 99%
“…The elevation of serum NSE caused by unidentified hemolysis will be considered as abnormal results, which may affect the clinical decision‐making. Inspiration from several studies that have attempted to derive reference values from patient samples, the alternative way is to re‐establish the NSE reference interval including these invisible hemolysis specimens.…”
Section: Introductionmentioning
confidence: 99%